INTERFAITH DIALOGUE IN ISLAMIC RELIGIOUS EDUCATION - Rosidah, Umi; Tobroni, Tobroni; Faridi, Faridi (Jurnal Konseling Pendidikan Islam, 2024)
The aim of this research is to examine interfaith dialogue in Islamic religious education. The method employed in this study is a qualitative approach with literature analysis. The results of the analysis conclude that obstacles to interfaith dialogue include distrust, prejudice, and a lack of understanding. These factors can impede the formation of harmonious relationships among individuals with diverse religious backgrounds. To address these challenges, ethical behavior in dialogue is crucial. Ethical conduct in interfaith dialogue involves sincere listening, respectful communication, and the avoidance of insults or confrontations. This forms the foundation upon which productive, mutually respectful, and mutually beneficial interfaith dialogue is built.